WEIGHTING ANALYSIS CRIMINALIZATION IN CRIME FILICIDE CRIME BASED ON PERSPECTIVE CRIMINOLOGY (THEORY POSITIVIS CRIMINAL) - Jevon Verrell Yosuaria Sitompul; Abdul Kholiq (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Filicide is a criminal act of murder committed by a parent against their own child, becoming one of the most complex forms of crime criminologically because the perpetrator is the party who is legally most responsible for the victim's safety. This study examines the provisions for aggravating filicide punishments in Indonesian positive law and analyzes the perpetrator's criminogenic factors through the perspective of the criminal positivist theory developed by Lombroso, Ferri, and Garofalo. The method used is a juridical-normative with a literature study of several court decisions. The results of the study indicate that the judge's considerations in aggravating punishments have not fully integrated the perpetrator's biological, sociological, and psychological factors systematically, so that standardized criminological guidelines are needed to produce more proportional and just decisions.